QUASI STATIC CHARACTERISTICS SIMULATION CARÃâÃâS TIRE WITH FINITE ELEMENT METHODS - TRI YURINDATAMA (NIM : 13107031); Dosen Pembimbing : Rachman Setiawan, S.T., M.Sc., Ph.D., DANAR
Most of the local tire companies in Indonesia do trial and error in design of its tire. The method is usually done in the design of its tires by doing variations of the component materials.Then made theirs prototype manufacturing and testing. If the tire characteristics resulting from this test does not match the desired spesifications, thenperformed a redesign view of different material combinations of the previous tire. In fact, to obtain the composition according to any one type of material from any components of the tire needs to be done by experiments that are not easy and it took quite a long time. Therefore, to sgorten the time of tire research, methods need to be other variations, i.e. variations in cross-sectional geometry and the variation of the tire tread. In this final project will be used three samples of the same size standard of car tires, but each has a different brand, than remodeled in the computer (using CAD) and performed simulations of loading (using finite element method) with the rim width variations and pressure variations. This simulation includes modeling and analysis of quasi-static (rim mounting, pressurization, dan vertical load). The results of this simulation show that the same standard tire sizes and magnitude of loading are given the same, but different brand, has different characteristics of stress and stiffness curves. Each stiffness curve can be approximated by third order polynomial equation. Maximum axial stress that occurs in bead core was about 540 MPa. From the results of verivication, the magnitude of errors that occur in these simulations is 3,23% to 22.22%